Speeches of Chief Ministers at 49th Meeting of the National Development Council at New Delhi on 1st September, 2001 Arunachal Pradesh Bihar Delhi Himachal Pradesh Karnataka Madhya Pradesh Nagaland - Planning Commission (Planning Commission, 2001)
We are meeting to consider the approach to the 10th Plan when the Indian economy - and indeed the global economy - has slowed down. For those of us who are on the geographic and economic periphery for the nation, the effects of also down in the national economy can have an exaggerated impact, as our own State economies are small and lack the resilience to absorb shocks of any magnitude. Planning Commission has envisaged an annual growth rate of 8% of GDP (Gross Domestic Product) at the end of the Tenth Plan period. This vision necessarily calls for substantial investment. Hard decisions and missionary zeal will be needed to meet these visionary aims.
National Development Council
Planning Commission